Cocrystal of phloretin with isoniazid: preparation, characterization, and evaluation. Issue 16 (6th April 2023) - Lu, Zhongyu; Chen, Hankun; Mo, Jiaxin; Yuan, Xiaohong; Wang, Dawei; Zheng, Xianhui; Zhu, Wei
Abstract : Phloretin and isoniazid formed new cocrystal and the structure, solubility and antitumor activities were study. Abstract : Phloretin (Phl) is a natural flavonoid compound with wide range of biological activities but demonstrates poor water solubility and limited pharmacological effects. In this study, one cocrystal of phloretin–isoniazid (Phl–Inz) was prepared successfully using the solvent evaporation method. The physical properties of cocrystal were characterized by differential scanning calorimetry (DSC), thermogravimetric analysis (TG), powder X-ray diffraction (PXRD), Fourier-transform infrared (FT-IR) and single crystal X-ray diffraction (SCXRD). The Hirshfeld surface analysis explained further interactions in the cocrystal. The solubility test showed that the solubility of the cocrystal was increased at pH 1.2 and pH 6.8 compared to that of the pure drug. The test in vitro simulated gastrointestinal digestion showed that the release of phloretin in the cocrystal was better than that in the pure phloretin. The results of the DPPH and ABTS scavenging activity showed that the in vitro antioxidant activity of the cocrystal was improved. The anticancer assay exhibited improved cytotoxicity in the Phl–Inz cocrystal as compared with the pure Phl.